Preparation and Characterization of Carrageenan-Modified Starch-Egg White Protein Composite Gels - CUI Yaxue, LI Wenzhao, YANG Xiaofei, YAN Feng, ZHANG Jiaping, RUAN Meijuan (Shipin Kexue)
Ternary composite gels consisting of carrageenan, hydroxypropyl distarch phosphate and egg white protein were characterized for gel properties and microstructural characteristics. Meanwhile, the interaction between different modified egg white powders (P10, PHG14 and PHG21) and polysaccharides was investigated, as well as their effects on the properties of composite gels. The results showed that compared with carrageenan and a binary composite gel consisting of carrageenan and modified starch, the ternary composite gel showed an increase in gel strength and water-holding capacity, a significant increase in elastic modulus (G’), a significant reduction in relaxation time T23, a decrease in its relative peak area A23, and a decrease in freezable water content. The infrared spectra of the polysaccharide-protein composite gel showed an increase in amplitude and a slight shift in peak position. X-ray diffractometry revealed that the diffraction peak intensity of the polysaccharide-protein composite gel was weakened, implying a reduction in the degree of crystallinity. Microstructural observation by scanning electron microscopy (SEM) revealed that the interaction between the polysaccharides and egg white proteins facilitated the formation of stable, dense and uniform gel networks. Compared with P10, addition of PHG14 or PHG21 to the carrageenan-modified starch composite gel resulted in more stable gel properties and microstructure.